Long non-coding RNA LINC00520 promotes malignant progression of gastric adenocarcinoma through miR-519b-3p/HIF1A axis: LINC00520 enhances gastric adenocarcinoma progression - An, Jie; Niu, Yunfeng; Liu, Wei (Cellular and Molecular Biology, 2025)
Gastric cancer is a prevalent malignant tumor, characterized by high morbidity and mortality rates globally. Long non-coding RNAs (lncRNAs), a class of transcripts exceeding 200 nucleotides in length, are non-protein-coding molecules that exert crucial regulatory functions in cellular biology. Investigating the regulatory mechanisms of lncRNAs in gastric cancer is essential. This study aimed to elucidate the functional role and molecular mechanisms of LINC00520 in gastric cancer. Initially, the GEO database was screened for differentially expressed genes associated with the malignant progression of gastric cancer. Quantitative reverse transcription polymerase chain reaction (qRT-PCR) was utilized to ascertain the LINC00520 expression in gastric cancer tissues. Subsequently, cellular functional assays were conducted to investigate the potential effects of LINC00520 on cellular behavior. The interaction between LINC00520, miR-519b-3p, and HIF1A was examined through bioinformatics analysis, and their binding interactions were confirmed using dual-luciferase reporter gene assays and RNA immunoprecipitation (RIP) assays. Our findings revealed a marked increase in the LINC00520 expression in gastric cancer tissues. Overexpression of LINC00520 was observed to enhance the malignant progression of gastric cancer cells. Through bioinformatics analysis, dual-luciferase reporter assays, and RIP assays, we demonstrated that LINC00520 upregulated HIF1A expression by competitively binding to miR-519b-3p, thereby acting as a molecular sponge. In conclusion, this study indicates that LINC00520, which is highly expressed in gastric cancer, exerts its effects by targeting the miR-519b-3p/HIF1A axis. These insights provide a foundation for developing diagnostic and therapeutic strategies for gastric cancer.